1995
DOI: 10.1007/bf00130244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the foetal development of muscle in normal and double-muscled cattle

Abstract: Muscle differentiation was studied in foetal Semitendinosus muscle from normal cattle and those with the 'culard' gene of muscular hypertrophy sampled at 90, 130, 170 and 210 days of foetal life. The different fibre types were characterized by immunohistochemistry with antibodies specific to different isoforms of myosin heavy chains. The isoforms were separated by electrophoresis, identified by immunoblotting and quantified by ELISA. In double-muscled animals, there was a slower rate of differentiation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…This result was consistent with the pattern of expression of myosin isoforms observed by immunocytochemical detection, indicating the presence of more mature myosins in the muscles of normal than of double-muscled foetuses at the same gestational stage [6]. These observations confirm a delay in the degree of differentiation of double-muscled foetuses.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result was consistent with the pattern of expression of myosin isoforms observed by immunocytochemical detection, indicating the presence of more mature myosins in the muscles of normal than of double-muscled foetuses at the same gestational stage [6]. These observations confirm a delay in the degree of differentiation of double-muscled foetuses.…”
Section: Discussionsupporting
confidence: 89%
“…The hypertrophy of some superficial muscles, which results from the presence of inactive myostatin, is the consequence of an increase in the total fibre number [2] due to hyperplasia [3,4]. Picard et al [5,6] showed, in vivo and in vitro, that there was a variable delay in contractile differentiation of the 394 A. Listrat et al…”
Section: Introductionmentioning
confidence: 99%
“…This was accompanied by a reduced adipocyte hypertrophy with no effect on their number, and a decreased lipogenesis in WAT. In muscle, energy restriction from birth to weaning decreased cross-section area and increased the proportion of fast glycolytic fibres, which were not detectable at slaughter (Picard et al, 1995). Although the increase in lean-to-fat ratio at weaning is spectacular, it is generally less marked when slaughter occurs later, depending on the feeding following weaning (Berge et al, 1991;Greenwood and Cafe, 2007).…”
Section: Nutritional and Physiological Control Of Muscular And At Growthmentioning
confidence: 99%
“…The properties of DM muscles appear during foetal development (Picard et al, 1995;Deveaux et al, 2001). MSTN expression is detected from 16 days in bovine embryos (Kambadur et al, 1997) and is regulated throughout gestation (Deveaux et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This is likely to be the consequence of disinhibition of myoblast proliferation at crucial stages of myogenesis (Picard et al, 1998;Thomas et al, 2000;Deveaux et al, 2001). Muscle contractile and metabolic differentiation of DM animals is delayed compared to that of conventional animals (Gagniè re et al, 1997) as their muscles express fewer mature myosin heavy chains at the same gestational age during the first two-thirds of foetal life (Picard et al, 1995;Martyn et al, 2004). However, whether the delay of muscle differentiation is strictly related to the initial difference in proliferation or whether it is related to some other process has not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%